Corporate Board Attributes and Dividend Pay-out Policy: Mediating Role of Financial Leverage - TAHIR, Hussain; MASRI, Ridzuan; Rahman, Mahfuzur (Korea Distribution Science Association (KODISA), 2020)
The relationship between corporate board attributes and dividend payout is already established yet mediating role of leverage in not been examined in Malaysian market. Therefore, this study aims to examine the mediating effect of financial leverage on the relationship between corporate board attributes and the dividend pay-out policy. A sample of 203 non-financial firms listed on the BURSA Malaysia between 2005 and 2018 were analysed using SmartPLS 3.0. The findings show that there is a partial mediating effect of financial leverage on the relationship between board members age, board diversity and dividend pay-out policy. Financial leverage also mediates the relationship between number of women on board, CEO-duality and dividend pay-out policy. However, financial leverage doesn't mediate the relationship between board size and dividend pay-out policy. This study offers insights to policy-makers to develop a better corporate governance as well as a guidance to firms in the construction and implementation of their corporate governance policies in relation to financial leverage. This study also shed light on the influence of efficient corporate board attributes on dividend pay-out policy and financial leverage for firm growth. This study concludes that corporate board attributes impact capital structure and thus, firms may change its payout policy. © Korean Distribution Science Association (KODISA).